2012
DOI: 10.1159/000334826
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NT-proBNP, NGAL, and H-FABP May Predict Hemodynamic Relevance of Patent Ductus Arteriosus in Very Low Birth Weight Infants

Abstract: Background: Hemodynamically significant patent ductus arteriosus (hsPDA) is the most common functional cardiovascular disease in preterm infants. The necessity to treat hsPDA can neither be derived solely from clinical nor from echocardiographic criteria. Objective: The aim of this study was to establish non-invasive parameters which can differentiate hsPDA from non-hsPDA. Methods: Urinary protein levels of NT-proBNP, NGAL, and H-FABP were measured and correlated with the necessity of therapy for PDA. In 37 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 58 publications
(36 reference statements)
1
27
0
1
Order By: Relevance
“…Tosse et al found that U-NGAL in neonates with a birth weight below 1,500 g was higher if a PDA that needed either medical or surgical intervention was present than in neonates with no PDA or a PDA with no need for intervention [10]. They diagnosed the PDA by echocardiography on day 1–3 but the need for medical or surgical intervention was based on respiratory setback, oliguria or failure to thrive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tosse et al found that U-NGAL in neonates with a birth weight below 1,500 g was higher if a PDA that needed either medical or surgical intervention was present than in neonates with no PDA or a PDA with no need for intervention [10]. They diagnosed the PDA by echocardiography on day 1–3 but the need for medical or surgical intervention was based on respiratory setback, oliguria or failure to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…U-NGAL has been hypothesized to be increased in the presence of a PDA [10]. A shunt across a PDA may result in an unfavorable distribution of the cardiac output between the pulmonary and the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…NT-ProBNP is also found in the urine as small peptides undergo renal filtration (11). Studies measuring urinary NT-ProBNP levels in children are generally limited to the prediction and follow-up of hemodynamically significant patent ductus arteriosus (hs-PDA) in preterm infants (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that early biological markers were valuable for differentiating hsPDA from insignificant PDA [6,7]. The B-type natriuretic peptide (BNP) is one of the cardiac neurohormones released by the ventricles in response to increased wall stress and volume or pressure overload [8,9].…”
Section: Introductionmentioning
confidence: 99%